Neurodynamic characteristics of highly skilled badminton players - Korobeynikov, G. V.; Mischuk, D. M.; Korobeynikova, L. G.; Xu, S. (Ukrainian Journal of Medicine, Biology and Sport, 2020)
This study presents the analysis of the neurodynamic characteristics of highly skilled badminton players. Taking into account the fact that the effectiveness of highly qualified badminton players depends on the athlete`s ability to perceive, analyze and process information, it is very important to study their psychophysiological functions in order to monitor the athlete`s functional state and correct the training process. In modern sports science, the branch of sports psychophysiology is one of the most promising in the search for modern approaches to the training of highly qualified athletes. The study of psychophysiological characteristics provides additional information about the functional state of the athlete during training and competitive activities. It is well-known that sports results largely depend on the individual typological characteristics of a person, as well as on how these features are used to realize the full range of athlete`s capabilities. Much attention is paid to the development of methodological approaches allowing to assess the functional state of the athlete`s nervous system in modern sports science. But, in modern literature there are practically no articles dealing with the study of psychophysiological characteristics of badminton players, which determined the relevance of the research topic. The purpose of this research was to study the neurodynamic characteristics of highly skilled badminton players. Material and methods. 11 men and 22 women aged 18-19 years took part in the research of ne neurodynamic characteristics of highly skilled badminton players. The following methods were used: theoretical analysis and generalization of research, literary and methodological sources; psychophysiological research methods, mathematical and statistical processing of research results. Psychophysiological studies were carried out using the modern hardware-software computer complex "Multipsychometer - 05". We chose the tests "Reaction to a moving object" and "Functional mobility of nervous processes" to study the neurodynamic characteristics. Results and discussion. The study results showed that according to the balance of nervous processes, athletes demonstrate an average level of anticipation ability and stability of the test performance, with the prevalence of excitation processes over inhibitory ones. By the functional mobility of the nervous processes, badminton players demonstrate an average level of speed of mastering the skill of completing a new task, with an average speed of perception and processing of information. The parameters of reflectivity and impulsivity are balanced, but there is a tendency to indicators shift towards reflectivity. Conclusion. The results analysis confirmed that the neurodynamic properties were highly genetically determined and conservative. Therefore, we can assume that this level of indicators is sufficient to demonstrate high sport results in badminton.